Cognitive and social activities and long-term dementia risk: the prospective UK Million Women Study. (February 2021) - Floud, Sarah; Balkwill, Angela; Sweetland, Siân; Brown, Anna; Reus, Elsa Mauricio; Hofman, Albert; Blacker, Deborah; Kivimaki, Mika; Green, Jane; Peto, Richard; Reeves, Gillian K; Beral, Valerie
Summary: Background: Although dementia is associated with non-participation in cognitive and social activities, this association might merely reflect the consequences of dementia, rather than any direct effect of non-participation on the subsequent incidence of dementia. Because of the slowness with which dementia can develop, unbiased assessment of any such direct effects must relate non-participation in such activities to dementia detection rates many years later. Prospective studies with long-term follow-up can help achieve this by analysing separately the first and second decade of follow-up. We report such analyses of a large, 20-year study. Methods: The UK Million Women Study is a population-based prospective study of 1·3 million women invited for National Health Service (NHS) breast cancer screening in median year 1998 (IQR 1997–1999). In median year 2001 (IQR 2001–2003), women were asked about participation in adult education, groups for art, craft, or music, and voluntary work, and in median year 2006 (IQR 2006–2006), they were asked about reading. All participants were followed up through electronic linkage to NHS records of hospital admission with mention of dementia, the first mention of which was the main outcome. Comparing non-participation with participation in a particular activity, we used Cox regression to assess fully adjusted dementia risk ratios (RRs) during 0–4, 5–9, and 10 or more years, after information on that activity was obtained. Findings: In 2001, 851 307 women with a mean age of 60 years (SD 5) provided information on participation in adult education, groups for art, craft, or music, and voluntary work. After 10 years, only 9591 (1%) had been lost to follow-up and 789 339 (93%) remained alive with no recorded dementia. Follow-up was for a mean of 16 years (SD 3), during which 31 187 (4%) had at least one hospital admission with mention of dementia, including 25 636 (3%) with a hospital admission with dementia mentioned for the first time 10 years or more after follow-up began. Non-participation in cognitive or social activities was associated with higher relative risks of dementia detection only during the first decade after participation was recorded. During the second decade, there was little association. This was true for non-participation in adult education (RR 1·04, 99% CI 0·98–1·09), in groups for art, craft, or music (RR 1·04, 0·99–1·09), in voluntary work (RR 0·96, 0·92–1·00), or in any of these three (RR 0·99, 0·95–1·03). In 2006, 655 118 women provided information on reading. For non-reading versus any reading, there were similar associations with dementia, again with strong attenuation over time since reading was recorded, but longer follow-up is needed to assess this reliably. Interpretation: Life has to be lived forwards, but can be understood only backwards. Long before dementia is diagnosed, there is a progressive reduction in various mental and physical activities, but this is chiefly because its gradual onset causes inactivity and not because inactivity causes dementia. Funding: UK Medical Research Council, Cancer Research UK.